Acceptance of New Standards for Financial Inclusion by Financial Service Providers in Bangladesh - Noor, Md Asad; Hossain, Tanjela; Shirazi, Hasan (South Asian Journal of Social Sciences and Humanities, 2022)
This study looked at the readiness of investors to raise the post-COVID 19 year, using access  to financial services as a consideration of their customer’s financial expectations in the future.  Standard of living in the financial expectations of their customer. A random sampling  modeling method and a survey-based research method were also used in this study. A sample  of the research methodology was also used in this study. A total of 110 respondents from the  insurance, financial, and banking and non -banking sectors in Bangladesh participated in the  survey and provided responses. Hypotheses were tested using descriptive and inferential data,  with a threshold of significance of 5 percent considered significant. There has been a  significant link between Bangladesh’s socio-economic progress and the adoption of financial  intermediation as a new norm in financial transactions, according to the findings. Public  finance agencies and individuals are encouraged to create a conducive environment in  developing financial technology as a driver of investment in Bangladesh’s rapid growth, it is  expected.
Keywords: Covid-19; Financial Inclusion; Financial Service Provider; Financial Transaction; Green Finance; New Standard